Health Outcomes Masyarakat: Mengukur Seberapa Penting Peran BPJS Kesehatan di Kota Serang - Kurniawanto, Hadi; Anggriawan, Muhammad Angga; Rustandi, Tata (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Public health is very important and affects the quality of life of individuals and society as a whole. Community health outcomes refer to individual and population health outcomes that can be measured in various dimensions such as mortality rates, morbidity rates, quality of life, and so on. Studies on community health outcomes are very important because they can provide an overview of the health of a population and the factors that influence it. In Indonesia, BPJS Health is a health insurance program that all citizens must have. This program aims to ensure that all Indonesian citizens can access affordable and quality health services. The aim of this study is to measure how important the role of BPJS Kesehatan is in improving the health outcomes of people in Serang City. The research method used in this research is a survey method specifically designed to obtain information about the results or impact of health interventions or medical care on individuals or populations as measured in the form of changes in health status, whether clinical, functional or quality of life. The survey was conducted using a modified questionnaire from the US Health and Retirement Study (HRS). The sampling technique used purposive sampling, where the selected respondents focused on people who were over 45 years old and had been BPJS Health participants for more than 2 years. The results of the study explain that the role of BPJS Health on SRH Selft Rated Health, the number of diseases, the number of limitations in daily activities, and the number of difficulties in daily instrumental activities have a significant effect. This research shows that BPJS Health has an important role in improving public health in Serang City.